AN EMPIRICAL INVESTIGATION OF CONSUMPTION BEHAVIOUR IN SELECTED OIC COUNTRIES - Shaikh, Salman Ahmed; Ismail, Mohd Adib; Ismail, Abdul Ghafar; Shahimi, Shahida; Mohd. Shafiai, Muhammad Hakimi (Journal of Islamic Monetary Economics and Finance, 2018)
This study examines the consumption behaviour in Organization of Islamic Cooperation (OIC) countries. It presents empirical evidence on rational expectations permanent income hypothesis (RE-PIH) and tests whether the phenomena of myopia, liquidity constraints or loss aversion impede forward-looking consumption behaviour. It also attempts to measure the intertemporal elasticity of substitution. The empirical evidence defies the existence of consumption smoothing phenomena as postulated in RE-PIH. The results support loss aversion. The response of consumption to unexpected income changes is statistically significant in only one-third of the countries. In contrast, the response of consumption to expected income changes is statistically as well as economically significant in as many countries. The intertemporal elasticity of substitution is also statistically insignificant in most of the countries and the elasticity is generally not positive. For the Islamic finance industry, the results help in explaining the low penetration of equity-based risk sharing instruments. From the policy perspective, the excess sensitivity of consumption to income suggests that redistribution efforts to enhance incomes of poor could help in enhancing their consumption levels.